Health Promoting University Management Program in Realizing The Health Campus Society and Wellbeing in Andalas University 2022 - Mesa Fadila; Roni Ekha Putera; Ria Ariany (Faculty of Public Health, Andalas University, 2022)
A Health Promotion University is one of the public programs in an effort to create a healthy campus community in a comprehensive manner. Even though it is new, this program has a strategic and systematic role in the development of the community structure of the university environment. The purpose of this study is to find out how the management of a healthy campus program at Andalas University uses the system approach method by Azrul Azwar with input, process, output, impact indicators. The approach used is descriptive qualitative with data collection through document review, observation, interviews, and FGD with purposive sampling. Data were analyzed by codification/reduction, data display, and drawing conclusions. Data validity by source triangulation. The results of the study indicate that the management of the Andalas Health Promotion University has not been implemented properly based on; (1) program inputs are generally sufficient, both man, money, and material. Weaknesses are found in the method that has not been specifically formulated for program implementation guidelines at Unand, (2) The process has been carried out by Andalas University as a follow-up to the cooperation agreement with the Ministry of Health, but the work program planning has not been completed as a projection in achieving program goals and has not yet been included. in the Unand Strategic Plan. Organizing the Health Promotion University Management Team has been formed since 2019, but its position in the organizational structure at Andalas University is not yet clear, resulting in less effective coordination and communication in program implementation (3) The output of the Health Promotion University program has begun to be produced, but it is still very minimal because there are no program achievement indicators that should be contained in program planning. (4) The impact of this program can not be felt/measured because it is directly related to the output which cannot be obtained optimally.